Sexual scripts overlap scale : short version - Štulhofer, Aleksandar (Array, 2010)
Little is known about possible impact of sexually explicit material (SEM) or pornography use on young people’s sexual socialization. The efforts so far have been characteristically brief (one-item measures assessing self-rated influence of pornography on one’s sex life were often used) and direct – thus vulnerable to normative expectations and socially desirable answers. According to our conceptualization, pornographic imagery competes with other socially available sexual narratives in the process of sexual scripting, particularly in the formation of personal sexual scripts. It should be, therefore, possible to retrospectively assess the impact of SEM on sexual socialization by measuring the overlap between a pornographic and personal depiction of sex, which is what the Sexual Scripts Overlap Scale (SSOS) does. The SSOS has been recently found a useful tool in modeling mediated effects of early SEM use on sexual satisfaction of young adults. To facilitate wider application of this composite measure, a brief but more robust version of the scale (SSOS-S ; k=20) has been developed and validated using two online surveys. The paper includes description of the scale, including scale items and scoring procedure, as well as the results of reliability and validity tests (construct, convergent, and divergent validity were assessed).